c.1 - Bhargava, R. N. (Allahabad, 1979)
This book contains some of my papers on Public Finance published in various Indian and foreign journals. These are being brought out in a single volume in response to suggestions and requests from some of my students, colleagues and friends. These papers deal with important issues in Public Finance relating to federal finance, incidence of taxation, social accounting, taxable capacity, Public Finance in a socialist economy, etc. In addition, papers written on important problems of Indian Public Finances, such as, Union-State relations, public debt policy, sales taxation, economic administration, etc. have also been included in this volume. Although these articles were written on specific subjects they have an abiding interest as they deal with problems that are still important and engage the attention of experts as well as the layman. The publication of these papers in a single volume will enable the reader to acquaint himself with various issues in Public Finance and current problems of the Indian fiscal system.
Keywords: Finance, Public